Diagnostic algorithm for ameloblastic carcinoma. Issue 3 (17th September 2019) - Kase, Yutaro; Kasamatsu, Atsushi; Saito, Tomoaki; Koike, Kazuyuki; Iyoda, Manabu; Nakashima, Dai; Endo‐Sakamoto, Yosuke; Sunohara, Masataka; Shiiba, Masashi; Uzawa, Katsuhiro; Tanzawa, Hideki
Abstract: Ameloblastic carcinoma (AC) is an odontogenic malignant tumor which combines the histological features of ameloblastoma and cytologic atypia. The key point of the diagnosis and clinical characteristics of AC have not been well defined, as it is a rare type of tumor. Hence, in this study, we present' for better clarity the diagnostic flowchart for AC, ameloblastoma, and metastasizing ameloblastoma.